Critical Discourse Analysis of Teun A. Van Dijk Model on Marshel's Widianto's Roasting in The Show of Mata Najwa Muda Berkuasa: Apa Jadinya Jika Anak Muda Berkuasa Episode - Rojudin; Intan Sari Ramdhani (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
This study discusses Marshel Widianto's roasting video broadcast on Najwa Shihab's Youtube media with the title